Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s10549-021-06377-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the menstrual cycle on commercial prognostic gene signatures in oestrogen receptor-positive primary breast cancer

Abstract: Purpose Changes occur in the expression of oestrogen-regulated and proliferation-associated genes in oestrogen receptor (ER)-positive breast tumours during the menstrual cycle. We investigated if Oncotype® DX recurrence score (RS), Prosigna® (ROR) and EndoPredict® (EP/EPclin) prognostic tests, which include some of these genes, vary according to the time in the menstrual cycle when they are measured. Methods Pairs of test scores were derived from 30 ER-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Previous studies have established a correlation between the presence of estrogen receptors and estrogen signaling and the development of cancers, particularly breast carcinoma [23][24][25]. We conducted a more in-depth analysis of the expression pattern of estrogen receptors in various cancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established a correlation between the presence of estrogen receptors and estrogen signaling and the development of cancers, particularly breast carcinoma [23][24][25]. We conducted a more in-depth analysis of the expression pattern of estrogen receptors in various cancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…While our review of current literature found inconclusive evidence for statistically significant variability of RS associated with menstrual cycling, Haynes et al data suggest that variations in RS can be clinically significant, leading to reassignment of risk categories and possible subsequent changes in treatment recommendations. 53 Addressing this question would not require a large randomized trial. Instead, a relatively small study could be conducted in which serum hormone levels, tumor RS testing and menstrual history are obtained twice (at the time of breast biopsy and breast surgery) from premenopausal patients diagnosed with HR-positive HER2-negative breast.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the best study evaluating the possible effect of the menstrual cycle on RS is the 2021 study by Haynes et al . 53 The authors evaluated paired tumor samples of ER-positive breast cancer taken at breast biopsy and again at 1 to 4 weeks later along with corresponding serum hormone concentrations and menstrual cycle history. The authors predefined two different menstrual cycle windows: W1, corresponding to low estrogen and low progesterone, occurring very early or late in the menstrual cycle at days 1–6 or 27–35; and W2, corresponding to high levels of estrogen and low or high levels of progesterone, occurring at mid to late cycle on days 7–26.…”
Section: The Role Of the Menstrual Cycle On Prognostic Biomarkers And...mentioning
confidence: 99%
See 1 more Smart Citation